Profile of The Use of Antihypertension Drug and Blood Pressure Evaluation at Gresik Hospital - Prada Marwah Al kamilah; Lusiani Tjandra; Meivy Isnoviana; Ibrahim Njoto (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
A potentially fatal non-communicable disease is hypertension. Important organs like the brain, heart, kidneys, retina, big blood vessels (aorta), and peripheral blood vessels are in danger for harm as a result. Heart attacks and even death can result from hypertension. By avoiding and managing risk factors like smoking, sedentary lifestyles, a lack of fruits and vegetables, and obesity, it is crucial to work towards lowering the risk of hypertension. This study's objectives were to assess blood pressure and establish the profile of antihypertensive medicine use. Methods: Data for this retrospective analysis were gathered based on information from patient pharmacy records and medical records. Results: 33.7% hypertension sufferers aged 65-74 years, 62.2% women and 37.8% men, 38.9% The beta-blocker drug group with the drug that is often used Bisoprolol dose of 2.5 mg as much as 26.9 %, 88% in tablet dosage form, which is used in combination form with the rule of using once a day and 64.3% controlled hypertension. This is a retrospective study that obtained data based on medical record information and patient pharmacy data. Conclusion: Hypertension patients are usually aged between 65-74 years, mostly female. Antihypertensive drugs that are often used are in the beta blocker class which is a Bisoprolol dose of 2.5 mg in tablet, used in a single dose or/and combination. Sixty-four point three percent (64.3%) of patients have controlled hypertension.